Corrosion Mechanism And Kinetic Behaviour Of Refractory Materials In Contact With CaO-Al2O3-MgO-SiO2 Slags - S. Jansson; V. Brabie; L. Bohlin (The Southern African Institute of Mining and Metallurgy, 2004)
The rate of dissolution of solid MgO-C and doloma into liquid in CaO-Al2O3-SiO2-MgO slag at different temperatures was studied under conditions of forced convection by rotating cylindrical refractory specimens in a stationary crucible containing the molten slag. The corrosion rate was calculated from the change in diameter of the cylindrical specimens. Refractory specimens were 13 mm in diameter and 70 mm long. The specimens were rotated for15 to 120 minutes at speeds of 100 to 400 rpm in the molten slag. The rate of corrosion increased with temperature and with the rotating speed of the rod, and decreased when the slag was nearly saturated with MgO. The experimental results confirm the assumption that the diffusion of magnesium oxide through the slag phase boundary layer controls the corrosion process. The corrosion mechanism seems to be the dissolution of the refractory materials into the slag, followed by penetration of pores and grain boundaries and dispersion of the grains in the slag. Keywords: MgO-C refractory, doloma refractory, molten slag, corrosion rate, corrosion mechanism